2015
DOI: 10.1167/iovs.15-16683
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chitosan/Aptamer Targeting TGF-β Receptor II Thermo-Sensitive Gel for Scarring in Rat Glaucoma Filtration Surgery

Abstract: This study presents evidence that the antifibrotic effect of chitosan in combination with aptamer S58 is superior to chitosan alone in a rat GFS model. Chitosan/S58 gel may be considered to be a promising antifibrotic agent for a local drug therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Previous observations have indicated that TGF-β2 concentration is significantly higher in patients with either open-angle glaucoma (OAG) or POAG [11], which mark TGF-β2 as a novel therapeutic target for POAG. In fact, targeting TGF-β isoforms and/or related receptors has proven promising therapeutic targets in a glaucoma animal model [25]. For instance, in a rabbit model of glaucoma filtration surgery, subconjunctival injection of anti-TGF-β2 antibody CAT-152 significantly improved glaucoma surgery outcomes and reduced scarring [26].…”
Section: Discussionmentioning
confidence: 99%
“…Previous observations have indicated that TGF-β2 concentration is significantly higher in patients with either open-angle glaucoma (OAG) or POAG [11], which mark TGF-β2 as a novel therapeutic target for POAG. In fact, targeting TGF-β isoforms and/or related receptors has proven promising therapeutic targets in a glaucoma animal model [25]. For instance, in a rabbit model of glaucoma filtration surgery, subconjunctival injection of anti-TGF-β2 antibody CAT-152 significantly improved glaucoma surgery outcomes and reduced scarring [26].…”
Section: Discussionmentioning
confidence: 99%
“…The IOP percentage (IOP%) was calculated as follows: IOP% = IOP operated /IOP unoperated [14]. The IOP% decreased markedly on day 5 in the control group and on day 3 in the DED group; then, it gradually increased over time in both groups.…”
Section: Resultsmentioning
confidence: 99%
“…The histologic features of scar tissue formation include enhanced fibroblast proliferation, synthesis and secretion of collagen, and deposition of extracellular matrix. 23 Therefore, the inhibition of fibroblasts in the surgical field may attenuate scar tissue formation. Cyclosporin A suppresses collagen expression in fibroblasts.…”
Section: Discussionmentioning
confidence: 99%